Access to Open Educational Resources during the Pandemic: the case of the OER Community in the Portuguese Open University Repository - Bastos, Glória (2023)
The COVID-19 pandemic that affected the world in 2020 and 2021, imposed important changes in teaching and learning processes in many institutions, notably in Higher Education. During this period teachers and students had to access online quality resources which increased the importance of Open Educational Resources (OER). Universidade Aberta (Portuguese Open University) is the only university, in the Portuguese higher education context, that includes in its institutional repository an autonomous OER community. It was considered of particular interest to analyse access to resources made available in the OER community during the pandemic, verifying whether this scenario had an influence on access and download numbers. Results show that the number of OER archived in the repositories has been growing, but the most relevant difference is between years 2018 and 2019. During the analyzed two years of the pandemic (2020 and 2021) the number of new deposits had remain stable, but the number of these resources’ downloads is very significant showing an increase during the pandemic period. We conclude that this increase in use should be considered a valid argument to justify more internal actions to support the strengthening of the OER collection at the UAb, especially in the scientific areas with fewer deposits.